An Efficient Synthesis of 3,4-dihydro-2(1H)-pyrimidinones from Aldehyde Bisulfite Adducts using Recyclable Wang Resin Supported Sulfonic Acid Catalyst - Kumar K. Pavithran, Vinay; Rao, Vinti S.P.; Jaganmohan, Chikkanti; Mohanty, Sandeep; Kumar, Jaydeep; Rao Battula, Venkateswara; Kalyani, Kommineni; Kallam, Srinivasa R. (Letters in Organic Chemistry, 2022)
An efficient one-pot multicomponent synthesis multicomponent synthesis of 3,4- dihydropyrimidin- 2(1H)-ones has been developed from aldehyde bisulfite adducts, ethyl acetoacetate and urea using recyclable polymer-supported sulfonic acid catalyst. This new method provides several advantages over the previous synthesis, including high product yields, commercially viable, minimal workup operations and sustainable chemical practices.
Keywords: 4-dihydropyrimidin-2(1H)-ones